British junior elite track and field athletes` experience of maltreatment, psychological safety, and subjective vitality - Hurst, P.; Chatziefstathiou, D.; Stirling, A. (Journal of Sports Sciences, 2025)
In this study, we examined 1) the prevalence of maltreatment in British junior elite track and field athletes, 2) relationships between maltreatment, psychological safety, and subjective vitality, and 3) whether maltreatment is indirectly related to subjective vitality via psychological safety. Using a cross-sectional design, British junior elite track and field athletes (N = 254) completed measures of maltreatment (physical, psychological, non-contact sexual and neglect), psychological safety and subjective vitality. Results showed that nearly three-quarters experienced maltreatment in sport (74.4%). Psychological maltreatment was most frequently reported (70.5%), followed by neglect (50.8%), physical (31.5%) and non-contact sexual (24.0%). Psychological and physical maltreatment, and neglect were indirectly related to subjective vitality via psychological safety (effect size range = -0.27 to -0.11), whereas no relationship was shown between non-contact sexual maltreatment and psychological safety. In conclusion, maltreatment is prevalent in British junior elite track and field athletes and that those who experience physical and psychological maltreatment, as well as neglect, are more likely to report lower psychological safety, and in turn, lower subjective vitality. International and national organisations aiming to protect athlete well-being should target psychological safety in their safeguarding interventions by supporting and encouraging athletes to speak out about their concerns.